The role of capsule endoscopy in the evaluation and treatment of obscure-overt gastrointestinal bleeding during daily clinical practice: a prospective multicenter study. (July 2014) - Katsinelos, Panagiotis; Lazaraki, Georgia; Gkagkalis, Asterios; Gatopoulou, Anthi; Patsavela, Stamatina; Varitimiadis, Kostas; Mimidis, Kostas; Paroutoglou, George; Koufokotsios, Alexandros; Maris, Theofanis; Terzoudis, Sotiris; Gigi, Elena; et al.
Abstract Objective. Capsule endoscopy (CE) is most commonly performed to evaluate obscure gastrointestinal bleeding (GIB). However, at present the role of CE in patients with obscure-overt GIB especially during daily clinical practice is unknown. The aim of the present study was to investigate the diagnostic yield and the impact of CE on the management of patients with obscure-overt GIB. Material and methods. Between January 2007 and December 2011 we prospectively included all patients with obscure-overt GIB who underwent CE after negative bidirectional endoscopy. CE findings revealing the cause of bleeding, type of therapeutic intervention and clinical variables associated with positive CE and recurrence of GIB were evaluated. Results. One hundred and eighteen patients with a median age of 66 years (range 8–89 years) were enrolled in the final analysis. The overall diagnostic yield of the CE was 66.9%. The most common findings were angiodysplasias (33.1%), followed by ulcer (23.7%), and tumors (6.8%). Age (p = 0.001) and cardiovascular disease (p = 0.007) were significant clinical variables predicting the higher incidence of angiodysplasias. Specific therapeutic interventions were undertaken in 54 patients with positive CE (68.4%). Recurrence of GIB was observed in one patient with negative CE (2.6%) and 16 patients with positive CE (20.3%). Univariate and multivariate analysis showed high age and no therapeutic intervention as significant factors associated with recurrent bleeding. Conclusions. CE represents a promising diagnostic method in the investigation of obscure-overt GIB, with significant impact on its clinical management in daily clinical practice.